Feasibility and Therapeutic Potential of Peptide Receptor Radionuclide Therapy for High-Grade Gliomas. (May 2021) - Nemati, Reza; Shooli, Hossein; Rekabpour, Seyed Javad; Ahmadzadehfar, Hojjat; Jafari, Esmail; Ravanbod, Mohammad Reza; Amini, AbdolLatif; Nemati, Ali; Ghasemi, Mohammad; Keshmiri, Saeid; Dadgar, Habibollah; Assadi, Majid
Abstract : Purpose: This pilot study tested the principle that 177 Lu-DOTATATE may be applied to patients with high-grade gliomas (HGGs) that are either inoperable or refractory to the standard conventional treatments and also assessed whether this approach could be a viable therapeutic plan in this dilemma. Methods: In this prospective study, 16 subjects experiencing HGGs that were either inoperable or refractory to the standard conventional treatments were included. All the patients checked for somatostatin receptor expression on the tumors. The patients were treated with 1 to 4 cycles of IV 177 Lu-DOTATATE. The primary end point was radiological response after peptide receptor radionuclide therapy, and the secondary end point was improved quality of life using Karnofsky Performance Score and Eastern Cooperative Oncology Group score. Results: In total, 16 subjects (10 males and 6 females) with a mean age of 55.68 ± 13.17 years (26–73 years) participated in the study. Of them, 8 patients were new HGG cases, and 8 patients had recurrent tumors. The participants' responses to treatments were complete remission in 12.5% of (n = 2), partial remission in 31.25% (n = 5), disease stability in 18.7% (n = 3), and disease progression in 37.5% (n = 6). In total, pretreatment and posttreatment Karnofsky Performance Score and Eastern Cooperative Oncology Group scores did not improved ( P > 0.05). The patients were followed up from 1 month to 26 months (median, 3 months). Conclusions: This preliminary result suggests that peptide receptor radionuclide therapy using 177 Lu-DOTATATE may be associated with positive effects in patients with HGGs (grade III–IV). However, this approach should be evaluated in a more homogeneous group of patients with more favorable performance status.